2023
DOI: 10.1186/s12891-023-06995-6
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of anatomical parameters of anterior transpedicular root screw intervertebral fusion system of cervical spine

Sen-qi Ye,
Liu-jun Zhao,
Zhi-peng Hou
et al.

Abstract: Objective This study aims to investigate the feasibility of the anterior transpedicular root screw (ATPRS) intervertebral fusion system for the cervical spine and provide a basis for the design of the ATPRS intervertebral fusion system. Methods A total of 60 healthy adult cervical spine CT images examined from our hospital were selected, including 30 males and 30 females, with an average age of 39.6 ± 4.8 years. The image data was imported into Mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…So, the ATPRS technology, in theory, mitigates the risks associated with screw insertion. In our previous study, we have indicated the feasibility of the ATPRS intervertebral fusion system in the cervical spine ( Ye et al, 2023 ). The system comprises three primary components: the insert positioned between the upper and lower vertebral bodies, the first screw connecting the upper vertebral body and the insert, and the second screw connecting the lower vertebral body and the insert.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, the ATPRS technology, in theory, mitigates the risks associated with screw insertion. In our previous study, we have indicated the feasibility of the ATPRS intervertebral fusion system in the cervical spine ( Ye et al, 2023 ). The system comprises three primary components: the insert positioned between the upper and lower vertebral bodies, the first screw connecting the upper vertebral body and the insert, and the second screw connecting the lower vertebral body and the insert.…”
Section: Introductionmentioning
confidence: 99%
“…The system comprises three primary components: the insert positioned between the upper and lower vertebral bodies, the first screw connecting the upper vertebral body and the insert, and the second screw connecting the lower vertebral body and the insert. Besides, based on our previous radiographic study of the ATPRS fixed system, the screw hole positions in the cage were determined ( Ye et al, 2023 ). However, there is a lack of direct biomechanical study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation